2001
DOI: 10.1074/jbc.m101715200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Impairment of Human Erythrocyte Energy Metabolism through the Oxygen Radical-mediated Direct Activation of AMP-deaminase

Abstract: The effect of oxidative stress on human red blood cell AMP-deaminase activity was studied by incubating either fresh erythrocytes or hemolysates with H 2 O 2 (0.5, 1, 2, 4, 6, 8, and 10 mM) or NaNO 2 (1, 5, 10, 20, and 50 mM), for 15 min at 37°C. AMP-deaminase tremendously increased by increasing H 2 O 2 or NaNO 2 at up to 4 and 20 mM, respectively (maximal effect for both oxidants was 9.5 and 6.5 times higher enzymatic activity than control erythrocytes or hemolysates, respectively). The incubation of hemolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Inhibition of H 2 O 2 induced red blood cell hemolysis of methanolic extract was examined by the in vitro method described previously by Tavazzi et al [13] . The erythrocytes from human blood were separated by centrifugation and washed with saline or isotonic sodium phosphate buffer (pH 7.4) until the supernatant was colorless.…”
Section: Antihemolytic Assaymentioning
confidence: 99%
“…Inhibition of H 2 O 2 induced red blood cell hemolysis of methanolic extract was examined by the in vitro method described previously by Tavazzi et al [13] . The erythrocytes from human blood were separated by centrifugation and washed with saline or isotonic sodium phosphate buffer (pH 7.4) until the supernatant was colorless.…”
Section: Antihemolytic Assaymentioning
confidence: 99%
“…The stimulation of physical activity in the skeletal muscle of both rats (36) and trout (34) has also been shown to affect the distribution of AMPD between free and bound forms. In human erythrocytes, Tavazzi et al (37) demonstrated that reactive oxygen species are directly responsible for activation of AMPD through sulfhydryl group modification.…”
Section: Journal Of Biological Chemistry 3837mentioning
confidence: 99%
“…Cardiac AMPD may help regulate adenine nucleotide catabolism during myocardial ischemia (Thakkar et al, 1994) under oxidative stress conditions (Tavazzi et al, 2001), increased ADP (Chung and Bridger, 1976), and sustained ␤-stimulation (Hohl, 1999). In skeletal muscle in vivo, AMPD activity increase during muscular work is mediated by ADP, AMP, and pH (Wheeler and Lowenstein, 1979).…”
Section: Controlsmentioning
confidence: 99%